Playing Into the Hands of the Powerful: Extracting "Success" by Mining for Evidence in a Payments for Environmental Services Project in Matiguás-Río Blanco, Nicaragua. (May 2021) - Van Hecken, Gert; Kolinjivadi, Vijay; Huybrechs, Frédéric; Bastiaensen, Johan; Merlet, Pierre
Payments for Environmental Services (PES) are premised upon the provision of monetary incentives to induce land-use practices viewed to be beneficial for advancing tropical conservation. A recent article published by Pagiola et al. in this journal claims that PES successfully transitioned land-use from agricultural use in Matiguás-Río Blanco, Nicaragua to silvopastoralism through afforestation and hence associated improvements in carbon sequestration and biodiversity conservation. Building on contrasting perspectives from peasants and local organizations in the region for more than a decade, we illustrate why viewing relations like payment provision and adoption of land-use outcomes that disregard parallel voices of implicated actors is not only analytically imprecise, but risks being anti-ecological if such a decontextualized connection is used to show evidence that tropical conservation is being advanced. We argue that the effect of payments must be contextualized with: a) increasingly globalized and expanding commodity frontiers for which PES programs may actually further advance to the detriment of tropical conservation; and b) the assumptions made in the methodological approaches adopted to determine causality. In sum, we highlight the dangers of uncritically portraying narratives of "success" to scale up investment to further proliferate decontextualized conservation projects that may not ensure long-term outcomes. We propose responding to these potential dangers through more open, horizontal, and long-term engagement on both the criteria and the consequences of defining success in tropical conservation interventions with actors whose lives are directly affected by them.